After the "Doc Fix": Implications of Medicare Physician Payment Reform for Academic Medicine. (July 2016) - Rich, Eugene C.; Reschovsky, James D.
Abstract : The Medicare Access and CHIP Reauthorization Act (MACRA) introduces incentives for clinicians serving Medicare patients to move away from traditional "fee-for-service" and into alternative payment models (APMs) such as accountable care organizations and bundled payment arrangements. Thus, MACRA creates strong reasons for various teaching clinical services to participate in APMs, not only for Medicare patients but for other public and private payers as well. Unfortunately, different APMs may be more or less applicable to the diverse teaching physician roles, academic clinical programs, and patient populations served by medical schools and teaching hospitals. Therefore, this time of transition will complicate the work of academic clinical program leaders endeavoring to sustain the tripartite mission of patient care, health professional education, and research. Nonetheless, payment reforms promoted by MACRA can reward efforts to reinvent medical education to better incorporate value into medical decision making, as well as to give clinical learners the tools and insights needed to recognize their personal financial (and other) conflicts and navigate these to meet their patients' needs. This post-MACRA environment may intensify the need for researchers in academic medicine to stay independent of the short-term financial interests of affiliated clinical institutions. Health sciences scholars must be able to study effectively and speak forcefully regarding the actual benefits, risks, and costs of health care services so that educators and clinicians can identify high-value care and deliver it to their patients.